In Vitro Comparison of Different Invisalign® and 3Shape® Attachment Shapes to Control Premolar Rotation - Ferlias, Nikolaos; Dalstra, Michel; Cornelis, Marie A.; Cattaneo, Paolo M. (Frontiers in Bioengineering and Biotechnology, 2022)
Aim: To evaluate in vitro the differences of various Invisalign® attachments in their effectiveness during derotation of an upper second premolar in terms of forces and moments created and compare them to the 3Shape® box attachment as well as to no attachment at all. Materials and Methods: A Force System Identification (FSI) machine, comprising two load sensors, was used in this study. Sensor 1 was connected to the test tooth (i.e. upper second premolar) carrying a different attachment design, and the fixed sensor (Sensor 2) was connected to the base model. Once the corresponding aligner was passively seated on the teeth, 12 different setups (i.e. 11 different attachments and one setup with no attachment at all) were tested by rotating the test tooth 4.5° mesially and 4.5° distally, in increments of 0.45°. Results: The vertical rectangular attachments were able to generate the highest derotational moment on both mesial and distal rotations but also received the most side effects (intrusive force, torque, and tipping). The no-attachment setup performed least favorably in terms of derotational ability but exhibited the least side effects. In the y-axis, all attachments received a buccal root torque with a lingual force during disto-rotation and a lingual root torque with a buccal force during mesio-rotation. Conclusion: Attachments are necessary for derotating an upper second premolar. An aligner incremental change of more than 1° derotation can generate high moments. The vertical rectangular attachments perform best in derotations; however, they exhibit the most side effects. Finally, despite presenting the least side effects, derotation of a premolar with no attachment is not as efficient.